COMPETÊNCIAS INDIVIDUAIS E CAPACIDADE DE ABSORÇÃO DE EMPREENDEDORES: A PROMOÇÃO DA INOVAÇÃO E TECNOLOGIA DE MICRO E PEQUENAS EMPRESAS INCUBADAS NO PARANÁ - Machado, Suélen Pontes (2019)
Scientific and technologic development of a country must be encouraged to have a meaningful growth. In order to this issue prospection the Innovation Law number 10. 973 from 2004, enhance the establishment of Incubators to Technologic Base Enterprises (ITBEs) being assisted by universities, city halls and other public and private institutions. ITBEs are organizations prepared to sustain gaps and ease some resources to new business development. Entrepreneurs who want to incubate their enterprises must participate of a selective process. Thus, it was inquired about: how individual competencies and absorptive capacity are related with the incubation of micro and small enterprises from Paraná state? The absorptive capacity of new knowledge must have better results when sustained by basic know-how. The research aimed to analyse the individual competencies and the absorptive capacity, how are related to the incubation process of technological micro and small enterprises, from Paraná state. Therefore, there were some specific goals: to define individual competencies from entrepreneurs linked with Paraná incubators; to verify the absorptive capacity from those entrepreneurs; to describe the incubators profile; to characterize the selection process of these incubators; and to evidence technological innovation kinds developed by enterprises. Consequently, the methods to achieve the goals have been stated by a quantitative approach, supported by qualitative techniques to collect data. A survey was established as research strategy, supported by questionnaires with incubated entrepreneurs and interviews with ITBEs managers. Besides that, it was done a documental analysis (public notice, normative ruling) with incubators. This data triangulation was made with statistics analysis, evaluation and categorical content analysis. The data were collected between the months of November/2018 to January/2019. It was identified and sent questionnaires to 121 incubated enterprises in 15 active incubators in the state. From them, 60 questionnaires were right answered by entrepreneurs and 6 managers added to the interviews. This number is justified by the information overload, when those speeches have been alike. Achieving the results, it might infer that incubators search for individual who has competencies, even minimal, in technology, market, management, capital and entrepreneurship. Although, there are some entrepreneurs still immature, who need to achieve a better absorptive capacity to have a successful business. The incubator need to develop a sensitive job, according to specific features of each enterprise and entrepreneur, in order to identify gaps into the business. The lack of knowledge in management, financial, market and administration were mentioned by managers as main gaps to be developed by ITBEs.